A review of the migration of radioactive elements in clay minerals in the context of nuclear waste storage; Journal of Radioanalytical and Nuclear Chemistry; Vol. 331, iss. 9 - Wang C.; Myshkin (Mishkin) V. F. Vyacheslav Fedorovich; Khan V. A. Valery Alekseevich; Panamareva A. N. Anna Nikolaevna (2022, 2022)
Title screen